2015
DOI: 10.4067/s0717-97072015000300015
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Arsenic During Soil Treatment and Storage

Abstract: There are many studies in the area of identifying and measuring arsenic (As) and its species in soil samples. However, stability of total As, As(V) and As(III) during sample drying and storage has received little attention. The present study evaluates the stability of total As, As(V) and As(III) in four soils with differing agricultural uses and physicochemical properties. Moisture elimination conditions were evaluated, i.e. lyophilization for 1 day vs. drying at 50°C for 3 days, along with different storage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Lee and Kim (2013) reported that As(III) showed higher toxicity to Eisenia fetida than As(V). In the studied soils, As(V) and As(III) represented 75 712% and 12 7 6% of the total soil arsenic (Vargas et al, 2015). Thus, derived thresholds correspond mainly to As(V).…”
Section: Effect Of Arsenic On Earthworm Reproduction In Low Salinity mentioning
confidence: 98%
“…Lee and Kim (2013) reported that As(III) showed higher toxicity to Eisenia fetida than As(V). In the studied soils, As(V) and As(III) represented 75 712% and 12 7 6% of the total soil arsenic (Vargas et al, 2015). Thus, derived thresholds correspond mainly to As(V).…”
Section: Effect Of Arsenic On Earthworm Reproduction In Low Salinity mentioning
confidence: 98%
“…To prevent volatilization of As during the digestion process, a Teflon stopper with a 30-cm-long glass reflux tube was used (adapted from [40]). Then, total As concentration was determined by hydride generation-atomic fluorescence spectrometry (HG-AFS) under experimental conditions detailed in Vargas et al [4]. On the other hand, the total concentration of Cu was determined by atomic absorption spectroscopy (Flame-AAS).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…To date, most As remediation efforts have focused on rice grown on soils under anaerobic conditions, where As is predominantly like arsenite ((AsO 2 ) − ) [2,3]. However, remediation experiences on crops grown in soils under aerobic conditions, where arsenate ((AsO 4 ) 3− ) is the most common speciation of As (e.g., [4]), are much fewer in number. This knowledge gap is seen in Mediterranean areas such as central Chile despite their global importance due to the high diversity of food produced.…”
Section: Introductionmentioning
confidence: 99%